The Deaths of the Author : Reading and Writing in Time - Gallop, Jane, 1952- (Book collections on Project MUSE., 2011)
Post-structuralist attitudes to authorship as expressed by Roland Barthes, Jacques Derrida, Eve Kosofsky Sedgwick, and Gayati Chakravorty Spivak with particular attention to time and death.